Process for removing thiocyanate from a monomethyl amine solution
Patent Information
- Application Number
- CN202611485693.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]基于此,本申请提供一种从单氰胺溶液中脱除硫氰根的方法,以解决现有技术中对硫氰根的去除效果较差的技术问题
本发明公开的一种从单氰胺溶液中脱除硫氰根的方法,包括将单氰胺溶液通过至少一个充满吸附材料的吸附柱的过程,吸附材料的制备方法为将Fe3+负载于γ-Al2O3上,制得吸附材料Fe/γ-Al2O3。该吸附材料利用γ-Al2O3作为载体提供接触界面,表面吸附态Fe3+与液相SCN-发生络合反应,生成铁–硫氰酸根络合物Fe[(SCN)]2+、Fe[(SCN)2]+、Fe(SCN)3,这些血红色系络离子固定在γ-Al2O3固相表面,从而将液相SCN-去除。将其应用于单氰胺溶液除杂时,对SCN-的去除率可达97%以上,相比于普通γ-Al2O3,去除率提高了88.9%以上;在该吸附方法的应用中,当吸附材料变为红色,表示其吸附饱和,只需更换吸附柱即可,省去了传统方法将吸附材料从单氰胺溶液中过滤、固液分离的过程,操作简单方便;该方法单氰胺在流动状态下完成除杂,实现了连续工作,提高工作效率。
Smart Images

Figure CN122977404A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of monocyanamide production technology, specifically relating to a method for removing thiocyanate from a monocyanamide solution. Background Technology
[0002] Cyanamine is a chemical substance with the molecular formula NH₂CN. It is readily soluble in water, ethanol, ether, benzene, chloroform, acetone, etc., slightly soluble in carbon disulfide, and toxic. At 122℃, it transforms into dicyandiamide, an isomer of carbodiimide (H₂NCNHN=C=NH). It readily polymerizes; three identical aminocyanide molecules can combine to form a trimer compound, melamine. Cyanamine is unstable, a colorless, rhombic crystalline solid, hygroscopic, with a melting point of 42℃. It is insoluble in ethylene oxide and can volatilize with water vapor, making it toxic. A 50% aqueous solution is a colorless liquid with a specific gravity of 1.0724. Cyanamine has high solubility in water, is weakly acidic, and is completely miscible with water at 43℃. A 30% solution of cyanamine is an organic synthesis intermediate obtained by adding acid to an aqueous suspension of calcium cyanamide; it is widely used, especially in the synthesis of pharmaceuticals and pesticides, and can also be used as a plant growth regulator. However, in the existing production process, the monocyanamide products produced have a high content of ions such as ammonium, thiocyanate, iron, silicon, calcium, and magnesium. When the monocyanamide solution is left to stand for a long time, they will combine with each other and eventually form insoluble substances that precipitate out, causing the product color to be unstable and affecting the appearance of downstream products.
[0003] In the prior art, Chinese invention patent application number 202211481893.7 discloses a combined decolorization method and system for cyanamide, which uses high-pressure pulse combined with flocculant and resin to remove impurities from cyanamide. Although it is more effective than the conventional method of using flocculant and anion and cation resin to remove impurities from cyanamide, the removal effect on thiocyanate is still not ideal. Summary of the Invention
[0004] Based on this, this application provides a method for removing thiocyanate from a cyanamide solution to solve the technical problem of poor thiocyanate removal efficiency in the prior art.
[0005] The technical solution to the above-mentioned technical problems in this application is as follows: A method for removing thiocyanate from a cyanamide solution includes: passing the cyanamide solution through at least one adsorption column filled with adsorption material; wherein the adsorption material is prepared by the following method: S10. Preparation of Fe 3+ Impregnation solution: Take a Fe(NO3)3·9H2O solution with a concentration of 0.1–0.5 mol / L, slowly add dilute nitric acid dropwise, controlling the pH to 1–2, to obtain Fe 3+ Impregnation solution; S20. Mixing γ-Al₂O₃ particles with the Fe... 3+ The impregnation solution was mixed at a ratio of 1g:2-10mL, stirred evenly, and then soaked for a specified time. After filtration and solid-liquid separation, the loaded Fe was obtained. 3+ γ-Al2O3 particles; S30. The load Fe 3+ The γ-Al2O3 particles were dried to obtain the adsorbent material Fe / γ-Al2O3.
[0006] Preferably, in the above method for removing thiocyanate from cyanamide solution, the concentration of the Fe(NO3)3·9H2O solution in step S10 is 0.3 mol / L.
[0007] Preferably, in the above method for removing thiocyanate from cyanamide solution, the concentration of the dilute nitric acid in step S10 is 1-3 mol / L.
[0008] Preferably, in the above method for removing thiocyanate from a cyanamide solution, in step S20, the γ-Al₂O₃ particles are reacted with the Fe... 3+ The impregnation solution is mixed at a ratio of 1g:3-5mL.
[0009] Preferably, in the above method for removing thiocyanate from cyanamide solution, the soaking time specified in step S20 is 6 to 12 hours.
[0010] Preferably, in the above method for removing thiocyanate from cyanamide solution, in step S20, the diameter of the γ-Al2O3 particles is 1-3 mm.
[0011] Preferably, in the above method for removing thiocyanate from cyanamide solution, the drying in step S30 specifically involves maintaining the temperature at 100–120°C for 8–12 hours.
[0012] Preferably, the method for removing thiocyanate from the monocyanamide solution described above further includes, before step S20: rinsing the γ-Al2O3 particles with deionized water to remove surface powder, then drying and cooling to room temperature for later use.
[0013] Preferably, in the above method for removing thiocyanate from a cyanamide solution, the flow rate of the cyanamide solution through the adsorption column filled with adsorption material is 0.5–4 BV / h.
[0014] Preferably, in the above method for removing thiocyanate from a cyanamide solution, when multiple adsorption columns are provided, the cyanamide solution is passed through each adsorption column sequentially.
[0015] Compared with the prior art, this application has at least the following advantages: This invention discloses a method for removing thiocyanate from a cyanamide solution, comprising passing the cyanamide solution through at least one adsorption column filled with adsorption material, wherein the adsorption material is prepared by using Fe... 3+ An adsorbent material, Fe / γ-Al₂O₃, was prepared by loading Fe onto γ-Al₂O₃. This adsorbent material utilizes γ-Al₂O₃ as a support to provide a contact interface, allowing Fe to be adsorbed on the surface. 3+ With liquid phase SCN - A complexation reaction occurs, forming an iron-thiocyanate complex Fe[(SCN)]. 2+ Fe[(SCN)2] + Fe(SCN)3, these blood-red complex ions are fixed on the surface of the γ-Al2O3 solid phase, thereby immobilizing the liquid phase SCN. - Removal. When applied to the removal of impurities from cyanamide solutions, it is effective against SCN. - The removal rate can reach over 97%, which is more than 88.9% higher than that of ordinary γ-Al2O3. In the application of this adsorption method, when the adsorbent material turns red, it indicates that its adsorption is saturated, and only the adsorption column needs to be replaced. This eliminates the traditional process of filtering the adsorbent material from the cyanamide solution and separating solid and liquid, making the operation simple and convenient. This method completes the removal of impurities from cyanamide in a flowing state, realizing continuous operation and improving work efficiency. Attached Figure Description
[0016] Figure 1 This is a system diagram for removing thiocyanate from a cyanamide solution.
[0017] In the figure: first adsorption column 100, first liquid extraction tube 110, first liquid extraction valve 120, second adsorption column 200, second liquid extraction tube 210, second liquid extraction valve 220, standby adsorption column 300, feed valve 400, control valve 500, cyanamide feed tube 600. Detailed Implementation
[0018] It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of this invention can be combined with each other. The technical solutions of this invention will be further described below in conjunction with the embodiments of this invention, and this invention is not limited to the specific implementation methods described below.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in this specification is for descriptive purposes only and is not intended to limit the scope of this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0020] In one specific embodiment of this application, a method for removing thiocyanate from a monocyanamide solution includes: passing the monocyanamide solution through at least one adsorption column filled with adsorption material; wherein the adsorption material is prepared by the following method: S10. Preparation of Fe 3+ Impregnation solution: Take a Fe(NO3)3·9H2O solution with a concentration of 0.1–0.5 mol / L, slowly add dilute nitric acid dropwise, controlling the pH to 1–2, to obtain Fe 3+ Impregnation solution; The iron source in this scheme can be either Fe(NO3)3·9H2O or FeC6H5O7, with Fe(NO3)3·9H2O being the preferred choice in this application. The added dilute nitric acid is mainly used to adjust the Fe... 3+ The pH value of the impregnation solution is crucial. If the concentration of dilute nitric acid is too low, a large amount of dilute nitric acid solution is needed to lower the pH, which will dilute the overall iron ion concentration and reduce the iron loading of the activated carbon. If the concentration is too high, the local acidity will be too strong during dropwise addition, causing localized H+ ions to rise. + The sudden increase in concentration leads to a large number of carboxyl adsorption sites being occupied on the surface of activated carbon, reducing Fe... 3+ Loading capacity; therefore, further, the concentration of dilute nitric acid in this scheme is 1 to 3 mol / L, which can smoothly adjust the pH value and is not prone to local over-acidity. The amount of liquid added is moderate and will not over-dilute the iron liquid, thus balancing the adjustment effect and the iron loading efficiency.
[0021] S20. Mixing γ-Al₂O₃ particles with the Fe... 3+ The impregnation solution was mixed at a ratio of 1g:2-10mL, stirred evenly, and then soaked for a specified time. After filtration and solid-liquid separation, the loaded Fe was obtained. 3+ γ-Al2O3 particles; γ-Al₂O₃ has a high specific surface area and abundant surface hydroxyl groups, making it suitable for impregnating loaded Fe. 3+ This method ensures uniform iron dispersion. The γ-Al₂O₃ particles used in this scheme have high mechanical strength, are suitable for fixed beds, and are easy to fill. This application utilizes γ-Al₂O₃ as a carrier to provide a contact interface, where Fe is adsorbed on the surface. 3+ With liquid phase SCN - A complexation reaction occurs, forming an iron-thiocyanate complex Fe[(SCN)]. 2+ Fe[(SCN)2] + Fe(SCN)3, these blood-red complex ions are fixed on the surface of the γ-Al2O3 solid phase, thereby immobilizing the liquid phase SCN. - Remove.
[0022] As a preferred option, the γ-Al2O3 used in this application is a product that conforms to the chemical industry standard HG / T 3927-2020 "Industrial Activated Alumina", and uses spherical γ-Al2O3 particles with a particle size of 1-3 mm, a specific surface area ≥200 m² / g, a pore volume ≥0.5 mL / g, and a low sodium type (Na2O≤0.3%) to avoid introducing impurities.
[0023] Preferably, the γ-Al2O3 particles and the Fe 3+ The impregnation solution ratio is 1g:3-5mL, and the specified soaking time is 6-12 hours. During the impregnation process, low-speed stirring can be performed to prevent particles from rubbing against each other and causing powder loss; alternatively, the mixture can be left to soak, with the impregnation container gently shaken every hour to ensure proper contact between the γ-Al₂O₃ particles and Fe. 3+ The impregnation solution is fully in contact with the Fe, allowing the Fe to... 3+ It diffuses fully into the internal pores of γ-Al2O3 particles and adsorbs onto the hydroxyl sites on the alumina surface.
[0024] After solid-liquid separation, the particle surface can be quickly rinsed with a very small amount of deionized water to wash away the free ferric nitrate adhering to the outer surface of the particles. However, prolonged rinsing with large amounts of water should be avoided to prevent the removal of adsorbed Fe from the pores. 3+ Washing reduces the load.
[0025] S30. The load Fe 3+ The γ-Al2O3 particles were dried to obtain the adsorbent material Fe / γ-Al2O3.
[0026] Preferably, the drying process involves maintaining the temperature at 110–120°C for 8–12 hours, resulting in a light yellow Fe / γ-Al₂O₃. Because Fe… 3+ With liquid phase SCN - The complex formed by the complexation reaction is red; therefore, Fe / γ-Al₂O₃ is packed into an adsorption column to adsorb SCN from cyanamide solution. - When the adsorbent turns red, it indicates that it is saturated, and only the adsorbent in the adsorption column needs to be replaced. This eliminates the need for the traditional method of filtering the adsorbent from the cyanamide solution and performing solid-liquid separation, making the operation simple and convenient.
[0027] In a preferred embodiment, before step S20, the method further includes rinsing the γ-Al2O3 particles with deionized water to remove surface powder, then drying and cooling to room temperature for later use.
[0028] In another specific embodiment of this application, the flow rate of the monocyanamide solution through the adsorption column filled with adsorption material is 0.5 to 4 BV / h.
[0029] Furthermore, when multiple adsorption columns are set up, the cyanamide solution is passed through each adsorption column sequentially. That is, multiple adsorption columns are set up in series. In some cases, to ensure sufficient absorption and continuous production, a backup adsorption column can be set up. Each adsorption column's outlet pipe is equipped with a sampling pipe and a valve. If the cyanamide solution passes through a certain adsorption column and the Fe / γ-Al2O3 in that column turns completely red, it indicates that the adsorption column is saturated. If the cyanamide solution continues to pass through subsequent adsorption columns until the Fe / γ-Al2O3 in a certain adsorption column remains unchanged, it indicates that the SCN in the cyanamide solution is within acceptable limits. - Once fully adsorbed, the cyanamide solution can be taken from the sampling tube after this adsorption column. Therefore, one or two backup adsorption columns can be set up in the next stage. This way, when the first-stage adsorption column becomes saturated and needs replacement, the backup adsorption column can be used as the working adsorption column, allowing for online replacement of the Fe / γ-Al2O3 in the first-stage adsorption column without shutting down the system.
[0030] by Figure 1For example, as a schematic diagram of a system for removing thiocyanate from a cyanamide solution, a total of two working adsorption columns are set up: a first adsorption column 100 and a second adsorption column 200, and a first-stage standby adsorption column 300. The adsorption columns are connected in series. The cyanamide feed pipe 600 is connected to the inlet of each adsorption column. The outlet of the first adsorption column 100 is connected to the inlet of the second adsorption column 200 and the standby adsorption column 300. The outlet of the second adsorption column 200 is connected to the inlet of the standby adsorption column 300. The outlet of the first adsorption column 100 is equipped with a first liquid extraction pipe 110 and a first liquid extraction valve 120. The outlet of the second adsorption column 200 is equipped with a second liquid extraction pipe 210 and a second liquid extraction valve 220. Each adsorption column inlet is also equipped with a feed valve 400. During operation, the cyanamide solution is introduced into the first adsorption column 100 through the cyanamide feed pipe 600. At this time, the feed valves 400 at the inlets of the second adsorption column 200 and the standby adsorption column 300 are both closed. After the cyanamide solution completes adsorption in the first adsorption column 100, it enters the second adsorption column 200. After adsorption is completed in the second adsorption column 200, it is discharged from the second liquid extraction pipe 210. At this time, the control valve 500 on the pipeline between the first adsorption column 100 and the standby adsorption column 300 is closed, and the control valve 500 on the pipeline between the second adsorption column 200 and the standby adsorption column 300 is also closed. The standby adsorption column 300 is in a stopped state. When the first adsorption column 100 reaches adsorption saturation, that is, when the adsorbent material Fe / γ-Al2O3 turns red, it indicates that the adsorbent material in the first adsorption column 100 needs to be replaced. At this time, the feed valve 400 at the inlet of the first adsorption column 100 is closed, and the feed valve 400 at the inlet of the second adsorption column 200 is opened, allowing the cyanamide solution to flow directly into the second adsorption column 200. Simultaneously, the control valve 500 on the pipeline between the second adsorption column 200 and the standby adsorption column 300 is opened, and the standby adsorption column 300 is converted into a working adsorption column and put into use. After the cyanamide solution is adsorbed by the second adsorption column 200 and the standby adsorption column 300, it is discharged from the outlet of the standby adsorption column 300. At the same time, the adsorbent material in the first adsorption column 100 is replaced. Similarly, when the second adsorption column 200 reaches adsorption saturation, the control valve 500 of the pipeline between the first adsorption column 100 and the second adsorption column 200 is closed, and the control valve 500 of the pipeline between the first adsorption column 100 and the standby adsorption column 300 is opened. The standby adsorption column 300 then becomes a working adsorption column and is put into use. After the cyanamide solution is adsorbed by the first adsorption column 100 and the standby adsorption column 300, it is discharged from the outlet of the standby adsorption column 300. At the same time, the adsorbent material in the second adsorption column 200 is replaced. In this way, the adsorbent material can be replaced without stopping the system, ensuring the continuous operation of the entire system and improving work efficiency.
[0031] It is worth noting that the process temperature and process time involved in the above embodiments are all temperatures or times used in the experiment. Any reasonable adjustments made by those skilled in the art based on the process temperature and process time provided by the present invention, within the error range, should be included within the protection scope of the present invention.
[0032] The technical solution and effects of the present invention will be further illustrated below through specific embodiments.
[0033] 1. Experimental Materials and Methods 1.1 Experimental Materials The cyanamide solution used in this experiment had a mass concentration of 30% and was prepared by the applicant; other materials and reagents were commercially available and could be used directly without further purification.
[0034] 1.2 Experimental Methods Residual SCN was measured using spectrophotometry. - Concentration. SCN - The formula for calculating the removal rate is as follows:
[0035] η: SCN - Removal rate; Initial concentration, : Residual concentration.
[0036] 2.1 Example 1 Preparation of adsorbent material: Take 60 ml of Fe(NO3)3·9H2O solution with a concentration of 0.1–0.5 mol / L (Table 1), and slowly add 2 mol / L dilute nitric acid, controlling the Fe content... 3+ The pH of the impregnation solution was 1.5; four portions of γ-Al₂O₃ particles with a diameter of 1–3 mm were taken and Fe... 3+ The impregnation solution was mixed at a ratio of 1g:3mL and impregnated for 8 hours. The impregnation container was gently shaken every hour. Then, the mixture was filtered and the solid and liquid were separated. The mixture was then dried at 110℃ for 10 hours to obtain Fe / γ-Al2O3 sample. An appropriate amount of Fe / γ-Al2O3 sample was prepared according to this method for later use.
[0037] Impurity removal experiment of cyanamide solution: A 1cm thick layer of quartz sand was laid at the bottom of the adsorption column, followed by a uniform 10g layer of adsorbent material. Another 1cm thick layer of quartz sand was then laid on top to prevent the feed from eroding and disturbing the bed. 100ml of a 30% (w / v) cyanamide solution was passed through the chromatography column via a feed pump at a flow rate of 1 BV / h to obtain a purified cyanamide solution.
[0038] 2.2 Comparative Example γ-Al2O3 particles with a diameter of 1-3 mm were directly loaded into the adsorption column, and the other steps were the same as in Example 1.
[0039] Detection of residual SCN - Concentration, and calculate SCN - Removal rates are shown in the table below: Table 1 Detection data from Example 1
[0040] As can be seen from the table above, changing the concentration of Fe(NO3)3·9H2O solution during the preparation of the adsorbent material has a significant impact on the adsorption capacity of the obtained sample. When the same cyanamide solution is treated with the same purification process, the Fe(NO3)3·9H2O solution concentration of 0.3 mol / L, which corresponds to sample 3, significantly affects the adsorption capacity of SCN. - The removal rate was the highest at 90.3%, but the adsorption effect was still not ideal.
[0041] 2.3 Example 2 The other steps are the same as for sample 3, the difference being the γ-Al2O3 particles and Fe 3+ The impregnation solutions are specified in Table 2.
[0042] Detection of residual SCN - Concentration, and calculate SCN - Removal rates are shown in the table below: Table 2. Detection data from Example 2
[0043] Please refer to the table above for the application of adsorbent materials to SCN in cyanamide solutions. - During the impurity removal process, γ-Al2O3 particles react with Fe 3+ When the impregnation solution ratio is 1g: 3-5mL, it is effective for SCN. - The removal rate of SCN can reach over 90%, especially when the solid-liquid ratio is 1g:4mL. - The removal rate is the highest, reaching 97.3%. With the increase of the dosage of thiocyanate adsorbent material, the removal rate of SCN... - The removal rate of Fe no longer showed a significant change, indicating that Fe 3+ When the amount of impregnation solution reaches a certain level, the adsorption capacity of the prepared adsorbent material tends to stabilize. Considering the cost of raw materials, γ-Al2O3 particles and Fe can be selected. 3+ The impregnation solution ratio of 1g:4mL was used in the preparation of adsorbent materials.
[0044] 2.4 Example 3 The other steps are the same as for sample 8, except that the cyanamide solution is passed through the chromatography column at the flow rates described in the table below.
[0045] Detection of residual SCN - Concentration, and calculate SCN - Removal rates are shown in the table below: Table 3. Detection data from Example 3
[0046] As shown in Table 3, adsorption materials were used to adsorb SCN from cyanamide solution. - At that time, as the flow rate of the cyanamide solution increased, SCN - The removal rate of SCN showed a decreasing trend. When the flow rate was between 0.5 and 2 BV / h, the removal rate of SCN was [missing information]. - The removal rates of all three were above 97%, and there was no significant difference among them. When the flow rate increased to 3 BV / h, the removal rate of SCN was... - The removal rate was significantly reduced, possibly due to the excessively high flow rate of the cyanamide solution resulting in a short residence time and insufficient adsorption. Considering the overall removal efficiency, the optimal flow rate was selected as 2 BV / h.
[0047] The above embodiments are merely illustrative of several implementation methods of this application, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A method for removing thiocyanate from a cyanamide solution, characterized in that, include: The process of passing a cyanamide solution through at least one adsorption column filled with adsorption material; The adsorbent material is prepared by the following method: S10. Preparation of Fe 3+ Impregnation solution: Take a Fe(NO3)3·9H2O solution with a concentration of 0.1–0.5 mol / L, slowly add dilute nitric acid dropwise, controlling the pH to 1–2, to obtain Fe 3+ Impregnation solution; S20. Mixing γ-Al₂O₃ particles with the Fe... 3+ The impregnation solution was mixed at a ratio of 1g:2-10mL, stirred evenly, and then soaked for a specified time. After filtration and solid-liquid separation, the loaded Fe was obtained. 3+ γ-Al2O3 particles; S30. The load Fe 3+ The γ-Al2O3 particles were dried to obtain the adsorbent material Fe / γ-Al2O3.
2. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, In step S10, the concentration of the Fe(NO3)3·9H2O solution is 0.3 mol / L.
3. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, In step S10, the concentration of the dilute nitric acid is 1–3 mol / L.
4. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, In step S20, the γ-Al2O3 particles are mixed with the Fe... 3+ The impregnation solution is mixed at a ratio of 1g:3-5mL.
5. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, The soaking time specified in step S20 is 6 to 12 hours.
6. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, In step S20, the diameter of the γ-Al2O3 particles is 1 to 3 mm.
7. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, In step S30, the drying process specifically involves maintaining the temperature at 100–120°C for 8–12 hours.
8. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, Before step S20, the process also includes rinsing the γ-Al2O3 particles with deionized water to remove surface powder, then drying and cooling to room temperature for later use.
9. The method for removing thiocyanate from a cyanamide solution as described in claim 1, characterized in that, The flow rate of the cyanamide solution through the adsorption column filled with the adsorption material is 0.5–4 BV / h.
10. The method for removing thiocyanate from cyanamide as described in claim 1, characterized in that, When multiple adsorption columns are set up, the cyanamide solution is passed through each adsorption column in sequence.
Citation Information
Patent Citations
Combined decolorization method and combined decolorization system for cyanamide
CN115738951A